2015
DOI: 10.1080/15321819.2015.1040160
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of HIV, HBV, HCV, and HTLV among Pregnant Women in Southwestern Nigeria

Abstract: Sexually transmitted infections (STIs) are major public health challenge especially in developing countries. This study was designed to determine the prevalence of Hepatitis B virus (HBV), Hepatitis C Virus (HCV), Human immunodeficiency virus (HIV), and Human T-cell lymphotropic Virus type I (HTLV-I) among pregnant women attending antenatal clinic, in Ladoke Akintola University Teaching Hospital, Osogbo, and South-Western Nigeria. One hundred and eighty two randomly selected pregnant women were screened for HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 29 publications
7
29
2
Order By: Relevance
“…In the present study, the highest seroprevalance of HBsAg was among the age group 36-45 years. Similar results were obtainedin Southwestern Nigeria [28] and Northwest Ethiopia [32]. Opayele et al [28] and Molla et al [32] found the highest age range as the age group 40-44 in Nigeria and Bahir Dar (Ethiopia) respectively.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In the present study, the highest seroprevalance of HBsAg was among the age group 36-45 years. Similar results were obtainedin Southwestern Nigeria [28] and Northwest Ethiopia [32]. Opayele et al [28] and Molla et al [32] found the highest age range as the age group 40-44 in Nigeria and Bahir Dar (Ethiopia) respectively.…”
Section: Discussionsupporting
confidence: 76%
“…Similar results were obtainedin Southwestern Nigeria [28] and Northwest Ethiopia [32]. Opayele et al [28] and Molla et al [32] found the highest age range as the age group 40-44 in Nigeria and Bahir Dar (Ethiopia) respectively. Desalegn et al [35] found 30-35 years as the highest age range in Addis Ababa (Ethiopia).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…During the second half of the 1980s, several HIV-1/HTLV-1 co-infection events were reported in Europe, America, and Africa, especially in hemophiliacs, intravenous drug users, homosexuals and sexual workers [ 134 ]. Nowadays, HTLV-1 and HIV-1 co-infection is mainly investigated in South America and Africa [ 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 ], with prevalence ranging from 0.5 to 10.9% depending on the studies. Differences in regional endemicity, ethnic origin of the population, risk behaviors and study designs could account for such variability.…”
Section: Hiv-1 and Htlv-1 Co-infectionsmentioning
confidence: 99%
“…[5] In Nigeria, the estimated prevalence of HCV infection varies widely (0.4-14.7%) depending on the region and subpopulation being considered. [6,7] A common denominator among all the reported prevalence in Nigeria is the lack of generalizability as their data is not nationally representative.…”
Section: Introductionmentioning
confidence: 99%